Багатомірна оцінка рівня інтелектуального потенціалу ВНЗ та її практичне застосування - Драган, Олена Іванівна; Мазник, Ліана Валеріївна; Бергер, Аліна Дмитрівна (My University, 2018)
Обґрунтовується методика визначення рівня інтелектуального потенціалу, яка базується на розрахунку вагомості показників з системи показників рівня інтелектуального потенціалу, їх інтегральному оцінюванні, розробці таксономічних оцінок цього рівня.The method of determining the level of intellectual potential based on the calculation of the importance of indicators from the system of indicators of the level of intellectual potential, their integral estimation, and the development of taxonomic estimates of this level is substantiated. It is substantiated that in order to make an effective management decision regarding the impact on the level of intellectual potential, it is necessary to constantly search for the optimal interconnection between the set of economic, innovative and personnel components, the change of which forms the intellectual potential of the enterprise as a whole. It is established that the main feature of using methods of multivariate estimation (in particular, taxonomy) in this study is information on the confirmed quantitatively homogeneity of the aggregate of experts regarding local condensations or dilutions in the set of estimates from the system of indicators of the level of intellectual potential of higher educational institutions.
Keywords: інтелектуальний потенціал; інтегральний показник; таксономічна оцінка; intellectual potential; integral index; taxonomic evaluation; кафедра економіки праці та менеджменту; кафедра маркетингу